Relative paleoenvironmental adjustments following deglaciation of the Byers Peninsula (Livingston Island, Antarctica) - Ruiz-Fernández, Jesús (2018)
In the present context of fast warming in the Antarctic Peninsula (AP), understanding past and recent environmental dynamics is crucial to better assess future environmental responses in this region. Very detailed geomorphological maps can help to interpret the interaction between glacial, periglacial, and paraglacial systems. The Holocene environmental sequence on Byers Peninsula, an ice-free area in the westernmost part of Livingston Island (Maritime Antarctica), is still poorly understood. This paper focuses on the geomorphology of the Cerro Negro, a volcanic plug located on the southeast fringe of this peninsula. The distribution of landforms and deposits generated by different geomorphological processes provides insights into the Holocene environmental dynamics on Byers Peninsula. During the fieldwork campaign in January 2014, an accurate geomorphological map of Cerro Negro and its surroundings was generated. Four geomorphological environments were identified: hill, north slope, southern escarpment, and marine terraces and present-day beach. Periglacial landforms are abundant, especially patterned ground features (blockstreams, sorted stone circles, stone stripes). All these cryoturbation landforms, except blockstreams, are active under present-day climate conditions. In addition to a sequence of Holocene marine terraces and slope deposits, such as talus cones and rockfalls, there is a glacial moraine adjoining the northern slope of the hill. From the morphostratigraphic correlation between the active and inactive landforms, we infer three main phases describing the paleoenvironmental evolution in this area: (1) maximum glacial expansion; (2) Holocene glacial retreat, lake formation, and intense periglacial dynamics; and (3) deglaciation of the Byers Peninsula and widespread periglacial processes. The Cerro Negro has been a nunatak for most of the Holocene; the lake located near the summit of this hill appeared when most of the Byers Peninsula was still covered by glacial ice. This study constitutes an example of how an accurate geomorphological characterization of a small area can complement other approaches to generate a better understanding of the paleoenvironmental evolution in the region.